Pengembangan Laboratorium Basah Fakultas Perikanan dan Ilmu Kelautan Universitas Khairun sebagai Pusat Eduminawisata Inovatif - Abubakar, Salim; M. Abjan Fabanjo; Riyadi Subur; Gamal M. Samadan; Faizal Rumagia; Irham; Rina; Suryani (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
The Community Partnership Program (PKM) focusing on the development of the Wet Laboratory of FPIK UNKHAIR as an eduminawisata demonstrates the integration of academic resources with coastal-based tourism potential. This facility functions not only as a research and learning center but also as an interactive educational tourism site that combines marine literacy, aquaculture practices, and coastal conservation. Activities implemented include mangrove seedling cultivation using polybags and bamboo methods, aquaculture of milkfish, tilapia, shrimp, and mud crab, as well as the utilization of aquaponic–biofloc systems and water quality monitoring tools. The presence of mangrove species such as Sonneratia alba and Nypa fruticans further enhances ecological education and conservation values. Community involvement in training and creative economic initiatives strengthens local capacity while creating sustainable benefits. Student participation through academic recognition also supports the Merdeka Belajar–Kampus Merdeka framework. Overall, this program successfully integrates education, research, community service, and empowerment, positioning the Wet Laboratory as an innovative model of coastal eduminawisata that contributes to marine-based sustainable development.